Image challenge: Breast lesion in an immunocompromised patient. (October 2020) - Mehta, Ravi; Gibani, Malick M.; Chattaway, Marie Anne; Ghazy, Anan
Highlights: 47-year-old immunocompromised woman. Breast abscess caused by Salmonella Enteritidis. Initial isolate sensitive to ciprofloxacin, subsequent isolate resistant. Required surgical incision and drainage. Abstract: A 47-year-old immunocompromised patient was admitted with a 19-day history of worsening pain and swelling in her right breast. She did not improve with an empirical course of oral flucloxacillin. An ultrasound-guided aspiration of the lesion was performed, as well as a CT scan of her thorax, abdomen and pelvis.